Synthesis and antimycobacterial evaluation of N-substituted 5-chloropyrazine-2-carboxamides - Servusová, Barbora; Vobicková, Jana; Paterová, Pavla; Kubíček, Vladimír; Kuneš, Jiří; Doležal, Martin; Zitko, Jan (Bioorganic & medicinal chemistry letters, 2013)
To develop new potential antimycobacterial drugs, a series of pyrazinamide derivatives was designed, synthesized and tested for their ability to inhibit the growth of selected mycobacterial strains (Mycobacterium tuberculosis H37Rv, Mycobacterium kansasii and two strains of Mycobacterium avium). This Letter is focused on binuclear pyrazinamide analogues containing the -CONH-CH2- bridge, namely on N-benzyl-5-chloropyrazine-2-carboxamides with various substituents on the phenyl ring and their comparison with some analogously substituted 5-chloro-N-phenylpyrazine-2-carboxamides. Compounds from the N-benzyl series exerted lower antimycobacterial activity against M. tuberculosis H37Rv then corresponding anilides, however comparable with pyrazinamide (12.5-25 μg/mL). Remarkably, 5-chloro-N-(4-methylbenzyl)pyrazine-2-carboxamide (8, MIC=3.13 μg/mL) and 5-chloro-N-(2-chlorobenzyl)pyrazine-2-carboxamide (1, MIC=6.25 μg/mL) were active against M. kansasii, which is naturally unsusceptible to PZA. Basic structure-activity relationships are presented.
Keywords: vztahy mezi strukturou a aktivitou; Pyrazines; Anti-Bacterial Agents; Amides; Antitubercular Agents; antituberkulotika; antibakteriální látky; Mycobacterium tuberculosis; amidy; Structure-Activity Relationship; pyraziny